Epistemological and Methodological Considerations in International School Textbook Research - Sakadolskienė, Emilija (Pedagogika, 2015)
Many acknowledge a dearth of research regarding Lithuanian school textbooks. Educational institutions rely on reviews by select experts who provide advice during the approval process. Most extant research analyses content and its relationship to curriculum. Some have examined multicultural tolerance issues. Very few field studies have been done on the actual use of textbooks by teachers and pupils. On the other hand, Lithuanian teachers’ reliance on textbook material for the delivery of instruction is greater than in other European countries, according to international research. Therefore, an increase of formative or development research regarding textbooks is necessary. This article presents the need for an epistemological stance in textbook inquiry. It has been argued that you cannot construct convincing textbook research methodologies without a theoretical stance and that textbook research has been “underphilosophised”. Various philosophical positions have been proposed for textbook research, including positivism, critical theory, postmodernism, hermeneutics, neo-hermeneutics, post-colonialism, post-postmodernism, and others. Each dictates its own view of content, narrative, marginalization, point of view, prejudice and tradition. In terms of methodologies, traditional content analysis has been supplemented by hermeneutic, linguistic, discourse, semiotic, narrative, historiographic, cross-cultural, critical analysis. Contingency analysis is a relatively new mixed method that examines the relationship between text and image. Others analyze textbook questioning techniques, visual materials or the process of textbook production. One of the greatest shift in textbook research is the realization that users are the arbiters of knowledge and meaning, and their role as intermediaries must be examined in context. For these types of studies to flourish partnerships need to emerge between universities, textbook publishers, schools, and educational policy makers.